THE INFLUENCE OF PRIMA SERVICE ON CUSTOMER LOYALTY (Study on Barbershop Barbershop Business in Pekkae, Tanete Rilau District, Barru Regency) - Nurlia (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal